Multimodal Discourses of Power and Identity in Roblox User-Generated Worlds: A Critical Discourse Analysis - Intan Maulina; Jumino Suhadi; Devi Pratiwy (International Journal of Multidisciplinary Sciences and Arts, 2026)
Roblox has emerged as one of the most influential user-generated digital ecosystems, in which multimodal resources visual design, spatial organization, avatar customization, interface affordances, and linguistic interaction play a central role in the construction of identity and the negotiation of power. This study examines how power relations and identity positions are discursively produced across three highly popular Roblox user-generated worlds: Brookhaven RP, Adopt Me, and Bloxburg. Drawing on Multimodal Critical Discourse Analysis (MCDA), informed by social semiotics and critical discourse theory, the study analyzes screenshots, spatial configurations, and in-game chat interactions to uncover ideological meanings embedded in these environments. The findings demonstrate that hierarchical relations are reproduced through spatial zoning, access restrictions, monetized affordances, and avatar aesthetics that index wealth, status, and social legitimacy. Linguistic interactions further reinforce symbolic domination through gatekeeping, commands, and exclusionary practices. Collectively, these multimodal resources construct narratives of consumerism, meritocracy, and social stratification that shape how young users understand agency, belonging, and value in digital spaces. This article contributes to English Studies by conceptualizing Roblox worlds as multimodal texts requiring critical literacy, and to Information Technology by foregrounding how platform affordances structure discourse production and social relations.